Evaluation of Anti-inflammatory Nutraceuticals in LPS-induced Mouse Neuroinflammation Model: An Update - Catorce, Miryam N.; Gevorkian, Goar (Current Neuropharmacology, 2020)
It is known that peripheral infections, accompanied by inflammation, represent significant risk factors for the development of neurological disorders by modifying brain development or affecting normal brain aging. The acute effects of systemic inflammation on progressive and persistent brain damage and cognitive impairment are well documented. Anti-inflammatory therapies may have beneficial effects on the brain, and the protective properties of a wide range of synthetic and natural compounds have been extensively explored in recent years. In our previous review, we provided an extensive analysis of one of the most important and widely-used animal models of peripherally induced neuroinflammation and neurodegeneration - lipopolysaccharide (LPS)-treated mice. We addressed the data reproducibility in published research and summarized basic features and data on the therapeutic potential of various natural products, nutraceuticals, with known antiinflammatory effects, for reducing neuroinflammation in this model. Here, recent data on the suitability of the LPS-induced murine neuroinflammation model for preclinical assessment of a large number of nutraceuticals belonging to different groups of natural products such as flavonoids, terpenes, non-flavonoid polyphenols, glycosides, heterocyclic compounds, organic acids, organosulfur compounds and xanthophylls, are summarized. Also, the proposed mechanisms of action of these molecules are discussed.
Keywords: LPS